Analyzing the Options of Growth on Emerging Markets - ПироговНикита Константинович; СаломыковаО. А. (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
Real options analysis gets more and more attention in academic research and business practice. A lot of work is devoted to application of real options to business strategy formulation and implementation. Earlier effort was concentrated to adopt option valuation models to project and company valuation mostly in extractive industries. Recent research shows that real options approach has proven to be a useful analytical tool in any area with high uncertainty and large capital requirements (pharmaceuticals, biotechnology, internet, etc.). Growth real option has a special meaning for companies operating in highly uncertain environment. When buying a number of shares, investors acquire an opportunity and a right to participate in the future corporate results. Emerging capital and real markets can be characterized as highly uncertain and usually provide potential for growth. Therefore, growth real option is especially important for corporations operating on emerging markets, for example, in Russia, India and Brazil. Investments in such markets give an opportunity not only to participate in corporate results, but also to get benefit from country economic growth. Modern financial managers are highly interested in getting ability to analyze growth real options and incorporate them into company value. To do that we need to study the influence of growth options on corporate capitalization. Discovered growth option value drivers should allow managers purposefully and consistently use them to maximize corporate investment value. The main goal of this paper is to describe the results of research project which aimed to investigate the major factors affecting growth real option value.